From fields of rye to Eyckian grandeur new biographical data on Pieter Cristus (c. 1420-1475) - Verheyen, Jan (2024)
Recent archival finds fill some gaps in the biography of Pieter Cristus (c. 1420-1475), the painter who succeeded Jan van Eyck and who is considered the flagbearer of the highly esteemed Eyckian style in Bruges. Several spellings of his name occur but most often authors have chosen the Latinised version, Petrus Christus. Nonetheless, consistency demands to name him by his Middle Dutch name Pieter Cristus, just like all other fifteenth-century early Netherlandish painters. Two important aspects of Pieter Cristus’ life have now been uncovered, regarding his origins and regarding his Bruges residence. The painter’s odd family name Cristus is strongly related to his native town Baarle in the duchy of Brabant (now on the Belgian-Dutch border). The synthesis of numerous documents, including charters, aldermen’s deeds, notarial deeds, tax registers and fief enumerations – many of which were previously unpublished – enabled the construction of a comprehensive understanding of Pieter Cristus’ origins in Baarle. His relatives were clearly part of the local elites, taking up roles as a notary, financial expert, administrator, burgomaster or a village priest. One member of the family, probably a cousin of Pieter Cristus, was closely related to the Burgundian court. Even his presumed father, an expert in finance whose name was Peter Cristus, was found. The second part of the article deals with Pieter Cristus’ residence in Bruges. Just recently the location of his house was discovered in a forgotten and overlooked annuity register. The house, formerly owned by a mayor of Bruges and located in the middle of the international business quarter, testifies to the painter’s high social position, quite appropriate for a man with his background. The various finds, both in Baarle and in Bruges, substantiate a consistent picture of a painter who moved comfortably in high social circles.
Keywords: Christus, Petrus -- 1410-1473; Biografie